Genetic susceptibility to neonatal lung diseases - Somaschini, M.; Castiglioni, E.; Presi, et al., S. (Acta Biomedica Atenei Parmensis, 2012)
Advances in molecular genetics have enabled improvement of knowledge in pathogenesis and diagnosis of either monogenic or multifactorial neonatal lung diseases. Variants in genes regulating surfactant function and metabolism are implicated in some rare and common respiratory diseases. Congenital surfactant deficiencies are rare diseases due to mutations in genes encoding surfactant proteins and cause significant and often lethal respiratory failure in newborns and interstitial lung disease in older children. Diagnosis is made by molecular analysis and eventually confirmed by histological analysis of lung tissue. A multifactorial contribution, resulting from interaction between multiple genes and environmental factors, has been supposed for respiratory distress syndrome (RDS) and bronchopulmonary dysplasia (BPD). Several potential candidate genes, especially regarding surfactant proteins and cytokines, have been shown in association with these diseases. Genetic variants predisposing to RDS or BPD are usually polymorphisms which are not causative, but can increase susceptibility to the disease. Identification of infants at risk of disease can be useful to provide them individualized therapies.